PENGARUH KEPEMIMPINAN MELAYANI (SERVANT LEADERSHIP) DAN BUDAYA KERJA TERHADAP KINERJA GURU DI SMKS MUHAMMADIYAH KECAMATAN TANAH ABANG JAKARTA PUSAT - septi (Journal of Research and Publication Innovation, 2023)
The aims of this study were to determine, analyze and obtain a clear picture of whether or not there is: 1) The Influence of Servant Leadership on Teacher Performance at Muhammadiyah Vocational School, Tanah Abang District, Central Jakarta. 2) The Effect of Work Culture on Teacher Performance at Muhammadiyah Vocational School, Tanah Abang District, Central Jakarta. 3) The Influence of Serving Leadership on Work Culture at Muhammadiyah Vocational School, Tanah Abang District, Central Jakarta. In this study used is a quantitative approach. The population in this study is from Muhammadiyah Vocational School, Tanah Abang District, Central Jakarta, for the 2021 academic year, there are 195 teachers. In this study the authors used the slovin formula. From these calculations, the results obtained 131 people. So the number of samples studied was 131 teachers of Muhammadiyah Vocational School, Tanah Abang District, Central Jakarta. The results of this study are: 1) The results of the calculation of the t test value of Serving Leadership variable (X1) with a tcount of 7,955 and a significance of 0,000. Because tcount is greater than ttable (7.955 > 1.978) and the significance is less than 5% (0.000 <0.050) then Ha is accepted and H0 is rejected, it can be stated that Serving Leadership (X1) has a positive and significant effect on Teacher Performance (X3). The result of calculating the R Square value is 0.331. This shows that 33.1% Serving Leadership (X1) has an effect on Teacher Performance (X3), while the remaining 66.9% is influenced by other factors not examined in this study. 2) The results of the calculation of the t-test value of the Work Culture variable (X2) with tcount of 10,685 and a significance of 0,000. Because tcount is greater than ttable (10,685 > 1,978) and the significance is less than 5% (0.000 <0.050) then Ha is accepted and H0 is rejected, it can be stated that Work Culture (X2) has a positive and significant effect on Teacher Performance (X3). The result of calculating the R Square value is 0.470. This shows that 47% Serving Leadership (X1) has an effect on Teacher Performance (X3), while the remaining 53% is influenced by other factors not examined in this study. 3) The results of the calculation of the t test value of the Serving Leadership variable (X1) with a tcount of 9,588 and a significance of 0,000. Because tcount is greater than ttable (9.588 > 1.978) and the significance is less than 5% (0.000 <0.050) then Ha is accepted and H0 is rejected, it can be stated that Servant Leadership (X1) has a positive and significant effect on Work Culture (X2). The results of calculating the value of R Square is 0.416. This shows that 41.6% Serving Leadership (X1) has an effect on Work Culture (X2), while the remaining 58.4% is influenced by other factors not examined in this study.